Sumol+Compal : a challenging merger - Mariz, Sara do Nascimento Duarte (2013)
Founded in 2009, through the merger of two companies (Sumolis and Compal), SUMOL+COMPAL is the Portuguese leading company in the non-alcoholic beverages market. Due to its long history, most of the company’s products are somehow etched in the memory of the Portuguese. As a result of this merger, the product portfolio increased significantly, all the synergies created contributed to its success and the company achieved in 2011 a turnover of 331.6 million euros, a lower value than the one achieved in the previous year. Manuel Lopes, SUMOL+COMPAL’s CEO, was building a powerful Portuguese company; nevertheless, it had the potential to be even greater. Company’s sales were suffering a decrease and in the year of 2011, Portuguese sales volume dropped by 9.1%. The economic downturn, the competitive environment and the emergency of private labels were motives to rethink the company’s strategy. The differentiation strategy adopted in Portugal was being questioned, as well as the passive presence in international markets. Unlike the domestic market, sales in foreign countries had increased by 30%. Given this indicator, why not to increase the investment in those markets? The hypothesis of adopting a more aggressive internationalization strategy in order to contribute to the company’s growth is one of the central issues of this study. The other crucial aspect of analysis is related to the company’s strategy in the Portuguese market. In Portugal, the prices charged by SUMOL+COMPAL are high, its products have high quality, but the company’s leading position may be threatened. Thus, should the company continue to pursue its differentiation strategy in a market where the competition adopted the opposite strategy and is able to increase considerably its market share? These questions will be explored along this dissertation, discussing topics such as internationalization, growth strategies, differentiation and positioning. The main purpose of this paper is to identify and analyze the company’s strategies both in the national and international markets.